Darapladib for preventing ischemic events in stable coronary heart disease - Harvey D. White (2018)
BACKGROUND: Elevated lipoprotein-associated phospholipase A2 activity promotes the development of vulnerable atherosclerotic plaques, and elevated plasma levels of this enzyme are associated with an increased risk of coronary events. Darapladib is a selective oral inhibitor of lipoprotein-associated phospholipase A2. METHODS: In a double-blind trial, we randomly assigned 15,828 patients with stable coronary heart disease to receive either once-daily darapladib (at a dose of 160 mg) or placebo. The primary end point was a composite of cardiovascular death, myocardial infarction, or stroke. Secondary end points included the components of the primary end point as well as major coronary events (death from coronary heart disease, myocardial infarction, or urgent coronary revascularization for myocardial ischemia) and total coronary events (death from coronary heart disease, myocardial infarction, hospitalization for unstable angina, or any coronary revascularization). RESULTS: During a median follow-up period of 3.7 years, the primary end point occurred in 769 of 7924 patients (9.7%) in the darapladib group and 819 of 7904 patients (10.4%) in the placebo group (hazard ratio in the darapladib group, 0.94; 95% confidence interval [CI], 0.85 to 1.03; P = 0.20). There were also no significant between-group differences in the rates of the individual components of the primary end point or in all-cause mortality. Darapladib, as compared with placebo, reduced the rate of major coronary events (9.3% vs. 10.3%; hazard ratio, 0.90; 95% CI, 0.82 to 1.00; P = 0.045) and total coronary events (14.6% vs. 16.1%; hazard ratio, 0.91; 95% CI, 0.84 to 0.98; P = 0.02). CONCLUSIONS: In patients with stable coronary heart disease, darapladib did not significantly reduce the risk of the primary composite end point of cardiovascular death, myocardial infarction, or stroke. Copyright © 2014 Massachusetts Medical Society.